Asymmetric effect of crude oil price on the quality of environment in Nigeria: An application of non-linear ARDL - Aminu Hassan Jakada; Bello Alhaji Ibrahim; Ismail Aliyu Danmaraya; Aminu Muhammad Fagge; Abdulnasir T. Yola (Caspian Journal of Environmental Sciences)
The study aimed at examining the asymmetric effect of crude oil price on the quality of environment in Nigeria. The study utilizes the time series form of annual data from 1970 to 2019 and applies the model of NARDL (Non-Linear ARDL) to determine the short-run and long-run asymmetries. The results revealed that positive shocks in crude oil price reduces the amount of carbon emissions thereby enhancing the quality of the environment in the long run, while negative shock increases the amount of carbon emission and hence deteriorate the quality of the environment. In the short the positive shock increases the amount of carbon emissions while the negative shocks reduces the carbon emissions and also improve the quality of the environment. Nonetheless, the magnitude and sign of positive as well as negative shocks of crude oil price are essential in environmental management policies. Henceforth, on the basis of the sign as well as magnitude, the study recommends for more subsidy on clean energy as well as formulation of a favorable form of policies for the implementation of renewable form of energy such as solar by residential consumers and industries particularly during the period of low crude oil price.